Market microstructure and asset pricing: On the compensation for illiquidity in stock returns - Brennan, Michael J.; Subrahmanyam, Avanidhar (Journal of Financial Economics, 1996)
Models of price formation in securities markets suggest that privately informed investors create significant illiquidity costs for uninformed investors, implying that the required rates of return should be higher for securities that are relatively illiquid. We investigate the empirical relation between monthly stock returns and measures of illiquity obtained from intraday data. We find a significant relation between required rates of return and these measures after adjusting for the Fama and French risk factors, and also after accounting for the effects of the stock price level.